Uji Kinerja Alat Penggiling Jagung Merek Mahkota Tipe MCM 200 di Desa Paslaten Kecamatan Likupang Selatan - Sompie, Mutiara; Rantung, Ruland A.; Ludong, Daniel P. M. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
This research aims to 1) test and analyze the performance of the Mahkota brand corn grinder, type MCM 200, 2) examine the effect of the machine’s rotational speed (rpm) on the distribution and uniformity of the ground corn particle size, and 3) measure the fuel consumption of the San-Xiang brand R175A engine driving the corn grinder at specific speeds. The research was conducted in Paslaten Village, South Likupang Subdistrict, using an experimental method. Data were collected in tabular form and processed descriptively. Data collection involved three treatments. The results indicate that the performance of the Mahkota MCM 200 corn grinder powered by the San-Xiang R175A engine is still feasible for use. The highest working capacity was recorded at a rotational speed of 1293 rpm, achieving 174.08 kg/hour, while the lowest capacity was at 901.9 rpm, with 133.77 kg/hour. The effect of rotational speed on the distribution and uniformity of the ground corn particle size showed a lowest fineness modulus of 4.61 and particle size of 0.960 mm at 1293 rpm, and the highest fineness modulus of 4.75 and particle size of 0.991 mm at 901.9 rpm. The average fuel consumption at 1293 rpm was 112.5 ml, while at 901.9 rpm it was 58.5 ml.